The importance of cross-linguistic interaction in third language learning - Szabó Noémi (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2018)
Abstract. The issue of learning foreign languages is still receiving an increasing attention these days. According to the latest statistical data, learning foreign languages and speaking more than one language can still be counted as a peculiarity in Hungary. Surveying the current literature on the chosen topic, several works, studies and articles on trilingualism and third language acquisition (TLA) appear to be a matter of curiosity, for example Cenoz & Jessner, 2000; Cenoz, Hufeisen and Jessner, 2001; Fouser and Hufeisen, 2005; De Angelis, 2007. Cross-linguistic awareness deserves more attention in consideration of third language acquisition and trilingualism because this area of research is still counted as a neglected area in multilingualism research. Moreover, far too little attention has been paid to metalinguistic awareness related to TLA research in the educational context (Jessner, Allgäuer-Hackl & Hofer, 2016). Jessner, Allgäuer-Häckl and Hofer (2016) focuses on the understanding of multi-competence with regard to multilingual learners. The classroom activities described in the article have concentrated on multilingual, especially metalinguistic and cross-linguistic awareness. The results would seem to suggest that multilingual approaches to teaching and learning have a positive reference at the linguistic and metalinguistic levels as well. In the DMM, a so-called Multilingualism or M-factor unfolds as a property which comprises “a set of skills and abilities that the multilingual user develops owing to her/his prior linguistic and metacognitive knowledge” (Jessner, 2008, p. 275). This multilingual repertoire promotes new skills, which consist of three main parts: language learning skills, language management skills, and language maintenance skills. (Herdina and Jessner, 2002). The focus of the research proposal is teaching English/German as third language in the Hungarian educational context. The aim of the study is to investigate the influence of cross-linguistic awareness on third language acquisition. Flynn and Berkes's article (2012) gives the theoretical framework of the research which focuses on explanatory model (CEP) for multiple language acquisition with special attention to the relationship between Hungarian, German and English languages. The first research question is whether students’ level of multilingual awareness is higher at German minority primary schools in Hungary than at the Hungarian primary schools. The second question is how cross-linguistic influence affects the lexical repertoire in relation to the order of language acquisition (L2: German, L3: English, and vice versa).

Резюме. Питання вивчення іноземних отримує все більшу увагу в наші дні. Згідно з останніми статистичними даними, розмовляти більш, ніж однією мовою, все ще непоширене явище в Угорщині. Міжлінгвістична обізнаність заслуговує на більшу увагу при вивченні третьої мови та тримовності, оскільки ця сфера досліджень все ще враховується як пропущена область у дослідженні багатомовності. Більше того, надто мало уваги приділяється вивченню металінгвістичних навиків, пов'язаних з дослідженнями вивчення третьої мови (TLA) в освітньому контексті. Робота в класі, описана в статті, зосереджена на багатомовному, особливо металінгвістичному та міжмовному розумінні. Результати, здається, свідчать про те, що багатомовні підходи до викладання та навчання мають позитивні посилання на мовному та металінгвістичному рівнях. У центрі уваги – викладання англійської/німецької як третьої мови в угорському освітньому контексті. Метою дослідження є вивчення впливу міжмовної обізнаності на вивчення третьої мови. Перше питання в дослідженні полягає в тому, наскільки ступінь багатомовної обізнаності студентів є вищим у початкових школах німецької меншин в Угорщині, ніж у звичайних початкових школах. Друге питання полягає в тому, як впливає крос-лінгвістичний вплив на лексичний репертуар щодо порядку вивчення мови (L2: німецька, L3: англійська і навпаки).
https://kmf.uz.ua/wp-content/uploads/2021/02/limes-2018_tom-v_v-evfolyam.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008404
Keywords: multilingualism; holistic view; cross-linguistic interaction; metalinguistic awareness; Dynamic Model of Multilingualism; multicompetence approach